Influence of paper mill wastewater on reed chlorophyll content and biomass. (December 2018) - Su, Fangli; Dong, Linlin; Li, Haifu; Wang, Tieliang
Abstract: Studies on the influence of paper mill wastewater, which affects photosynthesis, on reed chlorophyll and biomass can provide a theoretical basis for the ecological restoration of wetland plants. The influence of different concentrations of wastewater (chemical oxygen demands (COD) of 300, 175 and 50 mgL −1 ) and different irrigation times (germination, blade-expansion, rapid-growth, heading and maturity stages) on the contents of chlorophyll a, chlorophyll b, total chlorophyll and chlorophyll a /b in reeds were tested in experimental pools that simulated the wetland ecosystem of the Liaoning Shuangtai estuary. The contents of chlorophyll a, chlorophyll b, total chlorophyll and chlorophyll a /b all increased significantly with increasing concentrations of wastewater, and their contents all differed significantly from each other. The contents of chlorophyll a, chlorophyll b and total chlorophyll were maximal when irrigated at the beginning of all growth stages with COD of 300 mgL −1 (C1 O) at 2.253, 0.458 and 2.711 mgg −1 fresh weight (FW), respectively, with irrigation at the rapid-growth stage and were minimal in the control plants at 0.142, 0.068 and 0.210 mgg −1 FW, respectively, with irrigation at maturity. Chlorophyll a /b was maximal at C1 O at 5.753 with irrigation at germination stage and was minimal in the control plants at 2.113 with irrigation at maturity. Reed biomass was maximal at C1 O at 3.26 kg, which was 2.76 times higher than the control. Reed biomass was positively correlated with the content of chlorophyll and with COD in the wastewater. Paper mill wastewater generally increased the content of chlorophyll and the net photosynthesis rate and enhanced the growth of reeds. Highlights: Different concentrations of wastewater and different irrigation times on the contents of chlorophyll in reeds were tested. The contents of chlorophyll increased with increasing concentrations of wastewater, they contents differed from each other. Reed biomass was positively correlated with chlorophyll content and the level of COD of the wastewater. Paper mill wastewater increased the content of chlorophyll and the net photosynthesis rate of the reeds. Paper mill wastewater enhanced the growth of the reeds.